RECICLAGEM: o que dizem professores de ciências do município de Portel - Pará? - REIS, Lauriana Barbosa (2024)
The relationship between man and nature exceeded the limits of survival. Population growth and consumption of processed and disposable products increased the amount and diversity of solid waste. The importance of sensitizing the human being so that they, act responsibly and consciously is evident, maintaining a healthy environment for this and other generations. This paper presents the results of a survey that aimed to know the concept of science teachers working in the final years of primary education on recycling; verify that science teachers address the topic recycling in the classroom; identify actions developed by science teachers related to recycling and; know the importance that science teachers attach to recycling. To achieve these goals we conducted a qualitative research and as data collection instrument used a questionnaire. The study subjects were seven teachers who teach science classes in the last years of primary school, ie from 6 to 9 years in public schools in the city of Portel, Pará. The data were analyzed using the principles of analysis content. Through research, we found that the surveyed teachers, worked on this issue in the classroom, and each has a way to do this, what was also clear is that even being a subject that is routinely treated in TV many teachers do not have the total control of the real meaning of the term recycling, assigning it the definition of reuse. This demonstrates the urgent need for investment and ongoing training for teachers. Only in this way, promoting changes in behavior and values in our students will be possible.